Acquisition of turkish grammatical categories in bilingual context - Kyuchukov, Hristo; Кючуков, Хрісто (Lesya Ukrainka Eastern European National University, 2019)
The paper presents results form a study on acquisition of Turkish grammatical categories by first grade Turkish speaking minority children in Bulgarian primary school. Two groups of children speakers of Turkish are tested: ethnic Turks and ethnic Roma. The Roma are Muslims and are also speakers of Turkish. Both groups speak the Northeast variety of Turkish, spoken in the surroundings of Varna, Bulgaria. The author examines the lexical reaches, syntax complexity and narrative knowledge of the children and predicts that the low results on mother tongue tests will be a reason for difficulties in the second language acquisition - Bulgarian. The author connects the results of mother tongue knowledge of the children with the language interdependence theory of Cummins (1991), where the level of the mother tongue is a predictor of second language acquisition.У поданій статті представлено результати проведеного дослідження, що присвячене опануванню граматичних категорій турецької мови учнями першого класу турецької мовної меншини в болгарській початковій школі. В цьому тестуванні взяли участь дві групи дітей, які спілкуються турецькою: етнічні турки та етнічні роми. Роми, котрі стали учасниками дослідження, є мусульманами та розмовляють турецькою. Обидві протестовані групи говорять на північно-східній різноманітності турецької мови, якою розмовляють на околицях м. Варна, Болгарія. Автор досліджує лексичний запас, синтаксичну складність та наративні знання дітей і робить припущення, що низькі результати під час тестування рідної мови можуть стати причиною труднощів при освоєнні другої мови болгарської. Автор пов’язує результати знань рідної мови у дітей з теорією взаємозалежності мови Кумінса (1991), згідно якої рівень володіння рідною мовою є предиктором вивчення другої мови.
Опанування граматичних категорій турецької мови у контексті двомовності.
Keywords: Turkish; mother tongue; bilingualism; Bulgaria; турецька; рідна мова; двомовність; Болгарія